Citicoline Treatment in Acute Ischemic Stroke: A Randomized, Single-Blind TMS Study - Premi, Enrico; Cantoni, Valentina; Benussi, Alberto; Gilberti, Nicola; Vergani, Veronica; Delrio, Ilenia; Gamba, Massimo; Spezi, Raffaella; Costa, Angelo; Padovani, Alessandro; Borroni, Barbara; Magoni, Mauro (Frontiers in Neurology, 2022)
Background Recent research on animal models of ischemic stroke supports the idea that pharmacological treatment potentially enhancing intrinsic brain plasticity could modulate acute brain damage, with improved functional recovery. One of these new drugs is citicoline, which could provide neurovascular protection and repair effects. Objectives The objective of this randomized, single-blind experimental study was to evaluate whether the treatment with Rischiaril® Forte was able to restore intracortical excitability measures, evaluated through transcranial magnetic stimulation (TMS) protocols, in patients with acute ischemic stroke. Methods Patients with acute ischemic stroke were recruited and assigned to an eight-week therapy of standard treatment (control group - CG) or CDP-choline (Rischiaril® Forte, containing 1,000 mg of citicoline sodium salt) added to conventional treatment (treatment group - TG). Each subject underwent a clinical evaluation and neurophysiological assessment using TMS, pretretament and posttreatment. Results A total of thirty participants (mean [SD] age, 68.1 [9.6] years; 11 women [37%]) completed the study. We did not observe significant changes in clinical scores after CDP-choline treatment (all p > 0.05), but we observed a significant improvement in short-interval intracortical inhibition (SAI) (p = 0.003) in the TG group compared to the CG group. Conclusions The eight-week treatment with citicoline after acute ischemic stroke may restore intracortical excitability measures, which partially depends on cholinergic transmission. This study extends current knowledge of the application of citicoline in acute ischemic stroke.